Ritanserin, a serotonin-2 receptor antagonist, inhibits functional recovery after cerebral infarction. Issue 1 (3rd January 2018) - Mizutani, Kenmei; Sonoda, Shigeru; Wakita, Hideaki
Abstract : It has been suggested that serotonin (5-HT) may be implicated in functional recovery after stroke; however, the underlying molecular mechanisms remain unknown. Here, the role of 5-HT was verified using ritanserin, a potent 5-HT2A receptor antagonist, and protein expression and modification were analyzed to further understand the association between paralysis recovery and molecular mechanisms in the brain. Experimental cerebral cortex infarctions were induced by photothrombosis in rats. Voluntary exercise was initiated 2 days after surgery. Motor performance was then measured using the rotarod test. Differences in protein expression and phosphorylation in the perilesional cortex were analyzed using western blot. In behavioral evaluations, performance in the rotarod test was significantly increased by exercise. However, there was a significantly lower value in time until falling after combined exercise and ritanserin administration compared with that of exercise alone. Protein expression analysis revealed that phosphorylation of protein kinase C (PKC) α, PKCε, and growth-associated protein 43 (GAP43) was significantly upregulated by exercise. These effects were attenuated by ritanserin administration. These data suggest that 5-HT may be related to the underlying mechanisms of exercise-dependent paralysis recovery, that is, exercise-dependent plasticity through the phosphorylation of PKC and GAP43.